Culture Of Postpartum Care In Indonesia - Qoyimah, Ilmiatus; Anggorowati, Anggorowati; Dwidiyanti, Meidiana (Jurnal Midpro, 2022)
The puerperium or postpartum period is defined as the period that begins after the expulsion of the placenta after the birth of the baby and ends when the reproductive organs return to their pre-pregnancy state and lasts for 40 days. During the postpartum period, there are various kinds of care that mothers get, one of which is culture-based care which can affect the care process. The purpose of this Literature Review is to obtain a theoretical basis that can support solving the problem being studied. The preparation of this article was carried out using the Literature Review method by conducting a search based on the keywords "postpartum mother care culture" in national journals and "postpartum mother care culture" in international journals using a database taken from Science Direct, Pubmed and Google Scholar published in 2016-2021 with both qualitative and quantitative research designs. The search was carried out on international and national journal sites using the literature study method. The results show that Indonesian women in various regions have different cultural traditions in each region. The tradition is in the form of a culture of care that is carried out by postpartum mothers or postpartum mothers. These cultures include the Posoropu culture from Aceh, Marapi from North Sumatra, the Karo treatment culture, Sundanese and traditional ceremonies performed during the maternal period in Pati district, Central Java. The search was carried out on international and national journal sites using the literature study method. The results show that Indonesian women in various regions have different cultural traditions in each region. The tradition is in the form of a culture of care that is carried out by postpartum mothers or postpartum mothers. These cultures include the Posoropu culture from Aceh, Marapi from North Sumatra, the Karo treatment culture, Sundanese and traditional ceremonies performed during the maternal period in Pati district, Central Java. The search was carried out on international and national journal sites using the literature study method. The results show that Indonesian women in various regions have different cultural traditions in each region. Conclusion: the tradition is in the form of a culture of care that is carried out by postpartum mothers or postpartum mothers. These cultures include the Posoropu culture from Aceh, Marapi from North Sumatra, the Karo treatment culture, Sundanese and traditional ceremonies performed during the maternal period in Pati district, Central Java.